A Numerical Classification for Killings - White, Richard (Advances in Social Sciences Research Journal, 2018)
Today, there is but one numerical designator for classifying killings. Title 28, Section 530C of United States Code designates three or more killings in a single incident as a “mass killing”. This paper argues that the single numerical designator is insufficient for distinguishing between “ordinary” and “catstrophic” killings, blurring the distinction between law enforcement and homeland security incidents. This paper proposes developing a broader classification system for the same reason that the FBI established the current threshold, specifically to clarify jurisdictional boundaries affecting budgets and determining agency capabilities. This paper proposes a numerical classification for killings based upon historical benchmarks that identifies seven different classes across the spectrum of killings. This paper contends that despite its seeming callousness, preparedness and response agencies can improve their efficiency and effectiveness through a numerical classification for killings.